Large language models in the professional training of future foreign language teachers: prompting technologies - MelnykА. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2026)
The article substantiates the pedagogically sound use of prompting techniques for applying large language models in the professional training of future foreign language teachers.The relevance of the study is determined by the transformative potential of artificial intelligence in education and the need for a systematic analysis of chatbot application mechanisms in the development of professionally oriented communicative competence in future teachers of English. Despite studentsʼ active use of digital language tools, existing research predominantly focuses on general pedagogical outcomes, leaving insufficient attention to strategies for effective interaction through prompt design. The aim of the article is to develop a typology of prompts and information verification strategies for the pedagogically sound use of chatbots in practical language training. The methodological foundation included theoretical and methodological analysis of scientific sources, comparative analysis of contemporary approaches, systematization and classification of prompt types, methodological modeling of a task complex across various types of speech activity, and a descriptive-analytical approach with illustrative examples. The study develops a systematized typology of prompting techniques (action prompt, scenario prompt, explanation prompt, supplementation prompt, and prompt for providing material for analysis) and substantiates the principles of their effective formulation, including grammatical correctness, clear structure, specificity, positively framed instructions, avoidance of CEFR-level requests, and iterative refinement through experimentation. Three information verification strategies (SEARCH, CREATE, and CHASE-IT) are proposed for checking the reliability, relevance, and academic integrity of generated content, which is critically important for reducing the risks of hallucinations, bias, and uncritical borrowing. The study demonstrates that interaction with chatbots can contribute to the development of all components of professionally oriented communicative competence ‒ linguistic, speech, linguosociocultural, and learning-strategic ‒ provided that students develop prompting skills and the ability to critically evaluate generated outputs. The practical value of the study lies in a coherent set of tasks for reading, speaking, and writing that supports the development of speech skills, metacognitive strategies, and digital literacy and can be used in curricula for the Practical Course in English for students of pedagogical specialties.